PERAN TIM PEMBIMBING IBADAH HAJI INDONESIA PEREMPUAN DALAM MANAJEMEN PELAYANAN HAJI (STUDI DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI JAWA TENGAH) - Lily Awanda Faidatin; Maryono; Ashari Mujamil (UIN Sunan Kalijaga, 2023)
The problem of periodic Hajj services requires optimizing the performance of the task force and institutional organizers of the Hajj pilgrimage. This study aims to determine and analyze the management of Hajj services at the Regional Office of the Ministry of Religious Affairs of Central Java Province. The points of interest in this research include the integration of Hajj services carried out and the role of female TPIHI officers in the implementation services. This research is a qualitative with a field study method that uses data collection techniques in the form of observation, interviews, and documentation. Data analysis used descriptive analysis of the inductive model and assisted by the theory of public service management. The results showed that the service was through 3 stages: pre-operational, implementation, and post-implementation of the pilgrimage. Service integration begins with a systematic recruitment and training pattern so that Hajj officers have the capability to carry out services to pilgrims.The role of female TPIHI in the management of Hajj services is evidenced by their contribution, from goal setting to service evaluation. In reality, female TPIHI officers are needed when guiding female pilgrims, especially guidance on feminine issues and assistance for female pilgrims who leave without a mahram while doing the Hajj.